Integrative Approaches to Patient-Centered Care: The Convergence of Psychology, Nursing, Health Informatics, and Health Assistance - Mohammad Fahad Aldehaian,; Hamdan Maflah M Al Harbi,; Abdulaziz Ibrahim Mohammed Alresheedi,; Rakan Obaidullh Matar Alferaidy,; Faisal Fayhan Alharbi,; Shujaa Obaid Shujaa Alamri,; Abdullah Ali Al Yahya,; Yousef Abdullah Battal Alresheedi,; Mohammad Awaidh Alharbi,; Khalid Saleh Sulaiman Alnughaymishi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Patient-centered care (PCC) emphasizes the holistic consideration of patients’ needs, preferences, and values in the healthcare process. As healthcare systems evolve, an integrative approach that incorporates the expertise of multiple disciplines—psychology, nursing, health informatics, and health assistance—is essential to achieving optimal patient outcomes. This manuscript explores how these disciplines converge to create a more collaborative, personalized, and effective healthcare model. By integrating psychological care, nursing interventions, technological advancements in health informatics, and the supportive roles of health assistants, healthcare systems can enhance the overall patient experience and improve clinical outcomes. This paper discusses the complementary roles of each discipline, the collaborative models that can be implemented, and the benefits and challenges of such integration. Ultimately, this approach has the potential to transform patient care by fostering patient autonomy, improving communication, and addressing the social, emotional, and physical dimensions of health.